Trends in doctor consultations, antibiotic prescription, and specialist referrals for otitis media in children: 1995-2003 - Plasschaert, Astrid I O; Rovers, Maroeska M; Schilder, Anne G M; Verheij, Theo J M; Hak, Eelko (Pediatrics (Evanston), 2006)
Reported trends regarding the incidence of otitis media and antibiotic prescription rates are inconsistent. Our goal was to assess changes in incidence of consultation rates, antibiotic prescription, and referral rates for otitis media in children over the years 1995-2003. A cohort study including all children aged 0 to 13 years within the research database of the Netherlands University Medical Center Utrecht Primary Care Network covering the period 1995-2003. Otitis media diagnoses were recorded according to the International Classification of Primary Care codes and antibiotic prescription according to the Anatomic Therapeutic Chemical Classification System codes. Otitis media incidence rates were calculated as episodes per 1000 person-years. Antibiotic prescription and referral rates were calculated per 100 otitis media episodes. From 1995 to 2003, the overall general practitioner consultation rates for acute otitis media and otitis media with effusion declined by 9% and 34%, respectively. In children aged 2 to 6 years and those aged 6 to 13 years, the incidence rates of acute otitis media and otitis media with effusion declined by 15% and 41% and 40% and 48%, respectively. In children <2 years of age, the incidence rates of acute otitis media and otitis media with effusion increased by 46% and 66%, respectively. Antibiotic prescription rates for acute otitis media and otitis media with effusion increased by 45% and 25%, respectively. The referral rate for acute otitis media did not change, whereas the referral rate for otitis media with effusion increased by 45%. Consultation rates for otitis media have changed considerably over the last decade, and so have antibiotic prescriptions and specialist referrals. The rising antibiotic prescription rate for otitis media causes concern, because this may induce increasing medical costs and antibiotic resistance.